Dekonstruksi Mitos Gaya Hidup Ekspatriat: Implikasi terhadap Edukasi Finansial dan Kesejahteraan Psikososial - Radhif Aryant Aurofiq; Rizky Syaiful Najib; Luqman Yusuf Habibie; Arrafi Aditya Lathiif; Ahmad Fauzi Ali (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study examines the expatriate lifestyle as a social myth that is often linked to prosperity, luxury, and upward mobility. These representations are widely circulated through digital media and public discourse. They tend to hide the more complex realities experienced by individuals living abroad. This research uses a qualitative approach with an ethnographic orientation to understand how these meanings are formed and experienced in everyday life. Data were collected through in-depth interviews with informants who are connected to expatriate contexts. The findings show that the ideal image of expatriate life often hides financial pressure, social adaptation challenges, and psychosocial strain. The persistence of this myth also shapes how individuals define success and manage financial decisions. It influences how they evaluate their own well-being. These findings highlight the importance of strengthening financial literacy and increasing awareness of psychosocial well-being in facing socially constructed lifestyle expectations.